Ox-eye windows with stained glass decoration - Ghosh, Ayan (2023)
Frederick Stevens’ design of large windows allowed plenty of natural light and a breeze to pass through, keeping the buildings ventilated and illuminated. This was a practical necessity because, at the time of its construction, buildings didn't have electricity. The BMC building was, in fact, the first building in Mumbai to be fully electrified before its inauguration.